2011
DOI: 10.1007/s00520-010-1075-7
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in cancer patients: a plea for a better awareness of the issue

Abstract: Weight loss turned out to be frequent and clinically significant. We believe that this sign should deserve major attention by the oncologists to pursue the benefits that early nutritional support prospectively yields in terms of quality of life and clinical outcome improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 51 publications
1
22
1
1
Order By: Relevance
“…The central study database was held at the Fondazione IRCCS Istituto Nazionale Tumori of Milan where data collected on each patient were entered, checked for quality and completeness and elaborated. Details on the study protocol and preliminary results on the first 1,000 patients have been recently published [9], and database was previously utilized for two publications, one on weight loss and its association with digestive and systemic symptoms [10] and one on a definition and classification of cancer cachexia [11]. …”
Section: Methodsmentioning
confidence: 99%
“…The central study database was held at the Fondazione IRCCS Istituto Nazionale Tumori of Milan where data collected on each patient were entered, checked for quality and completeness and elaborated. Details on the study protocol and preliminary results on the first 1,000 patients have been recently published [9], and database was previously utilized for two publications, one on weight loss and its association with digestive and systemic symptoms [10] and one on a definition and classification of cancer cachexia [11]. …”
Section: Methodsmentioning
confidence: 99%
“…44 In an ongoing study on the nutritional status of cancer outpatients 45 we recently found that in 689 ≥ 65-year old subjects the mean weight loss was 9.5% (median value 8.2%) and percentage of patients with a weight loss ≥10% of their usual body weight was 42.5%. Moreover, the percentage of patients with a Nutritional Risk score ≥3 was 61.2%.…”
Section: Prevalence Of Malnutritionmentioning
confidence: 98%
“…12 Studies have demonstrated a high prevalence of malnutrition in elderly patients: >10% weight loss in 71%, BMI <20 in 44%, Mini Nutritional Assessment (MNA) <24 and low serum albumin in 66%. 13 Malnutrition is an important prognostic determinant of treatment outcome. Low BMI is associated with fewer oncologic therapies and poorer survival.…”
Section: Nutrition and Cancer Treatment Outcomementioning
confidence: 99%